PENGARUH DIGITALISASI DAN KUALITAS LAYANAN TERHADAP KINERJA KEUANGAN DI BANK BSI CABANG PETTARANI - Widyawati Widyawati; Sudirman Sudirman (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the extent of the influence of digitalization of services including banking services and service quality that focuses on customer satisfaction on the financial performance of banks. This study uses qualitative and quantitative data, where the data obtained are analyzed numerically and statistically. The analysis procedure includes testing the reliability of the instrument, data distribution (normality), and testing other classical assumptions such as multicollinearity and heteroscedasticity. In addition, multiple linear regression analysis is also used to test the relationship between variables and test the strength of the model through the analysis of the coefficient of determination, simultaneous test (F), and partial test (T). Based on the results of the analysis, it was found that partially digitalization does not have a significant effect on the financial performance of banks and conversely service quality has a positive and significant effect on financial performance, the results of the simultaneous test show that digitalization and service quality together have a significant effect on performance. This finding strengthens that although partially digitalization does not have a significant effect, overall both simultaneously have a significant effect on financial performance.